Universality of Polarization Switching Dynamics in Ferroelectric Capacitors Revealed by 5D Piezoresponse Force Microscopy. (2nd April 2013) - Kim, Yunseok; Lu, Xiaoli; Jesse, Stephen; Hesse, Dietrich; Alexe, Marin; Kalinin, Sergei V.
Abstract Ferroelectric polarization switching is sensitively affected by phenomena on multiple length scales, giving rise to complex voltage‐ and time‐controlled behaviors. Here, spatially resolved switching dynamics in ferroelectric nanocapacitors are explored as a function of voltage pulse time and magnitude. A remarkable persistence of formal macroscopic scaling laws for polarization switching based on classical models down to nanoscale volumes is observed. These observations illustrate the persistence of the return point memory in the material and allow the thermodynamic parameters of defects controlling switching to be estimated.